Functional characterization of Saccharomyces cerevisiae TFIID and TFIIA - Ranallo, Ryan T., author; Stargell, Laurie A., advisor; Lumb, Kevin, committee member; Laybourn, Paul, committee member; Woody, Robert W., committee member; Suchman, Erica, committee member (Colorado State University. Libraries, 2000)
In eukaryotes, regulation of RNA polymerase II (pol II) transcription is mediated at many stages. Pol II transcription initiation involves the coordinate interactions of many general and gene-specific transcription factors. The general transcription factors (TFIIA, TFIIB, TFIID, TFIIE, TFIIF, TFIIH) function as factors necessary for accurate transcription initiation in vitro. One of the first steps in transcription initiation is the sequence-specific binding of general transcription factor TFIID to the core TATA element. TFIID is a multiprotein complex consisting of TATA-binding protein (TBP) and 14 TBP-associated factors (TAFs). As a potential rate-limiting step in initiation, TFIID binding the core element is regulated in many different ways via numerous protein-protein and protein-DNA interactions. Using a TBP mutant partially defective for TFIID formation in vivo we show that an intact TFIID complex is not required for transcription of all pol II promoters. In fact, a partially disrupted TFIID complex results in promoter specific transcriptional defects. Furthermore, our results support the notion that TAFs serve as potential, but not obligatory targets for transcriptional activators. Crystallographic and numerous other studies of TBP have led to the view that TBP-DNA interactions are regulated by TBP dimerization. Therefore, we hypothesized that TFIID oligomerization was a point of transcriptional regulation in yeast. Using biophysical techniques and immunological methods we show no evidence of TFIID dimers in yeast. Our findings challenge the hypothesis that TBP dimerization regulates DNA binding and therefore transcription initiation in yeast. The association of TFIID with promoter DNA in vivo is stimulated by another general transcription factor TFIIA. We hypothesized that TFIIA also makes contacts with TAFs in the TFIID complex. Using a variety of techniques we show that TAF40 makes direct contacts with TFIIA and TBP. Furthermore we show that the interaction between TFIIA and TAF40 is important for transcription in vivo. Functional analysis of TFIIA confirmed the TAF40-TFIIA interaction and perhaps identified a new TFIIA-TAF interaction. These studies highlight the importance of the TFIID-TFIIA interaction in transcription initiation. Finally, a more in-depth study of TAF40 identified multiple interaction surfaces, one of which is important for essential functions in yeast. The continuation of these studies may reveal novel regulatory mechanisms of transcription initiation in yeast.
Keywords: genetics